A review of the Japanese Cybocephalidae (Coleoptera: Cucujoidea) - Hisamatsu, Sadatomo (Zootaxa, 2013)
The Cybocephalidae of Japan is taxonomically treated. The following four species are recognized: Cybocephalus (Cybocephalus) nipponicus Endrödy-Younga, 1971, C. (C.) politissimus Reitter, 1898, C. (C.) chlorocapitis sp. nov., and Pastillus eminentithorax sp. nov. Also, species of the genus Pastillus are first recorded from the Palaearctic Region, and C. (C.) politissimus is first recorded from Japan. Cybocephalus (C.) flavocapitis Smith 2007 is newly designated as a junior synonym of C. (C.) politissimus Reitter, syn. nov. All species are described or redescribed. Dorsal habitus images, illustrations of male and female genitalia, and other important diagnostic characters are provided for all species. A key for identification of all Japanese taxa is also given.